Pengaruh Beban Kerja, Kompetensi, Dan Stres Kerja Terhadap Kinerja Karyawan Garmen Luwih Collection Grogak - BALI - Ni Putu Hindu Anggara Yani; Dewiwati Sujadi (Universitas Triatma Mulya, 2025)
The leadership team at Luwih Collection Grokgak-Bali Garment should prioritize monitoring and evaluating staff performance, since it directly impacts the company's capacity to accomplish its goals. This study aims to determine the extent to which the independent variables, namely workload (X1), competency (X2), and work stress (X3), affect employee performance at Luwih Collection Garment, Grokgak Bali. Additionally, the study seeks to identify which of these variables has the greatest impact on employee performance at Luwih Collection Garment, Grokgak Bali. The study consisted of 55 individuals. This research used the technique of sampling from a wider population. Data analysis involves the application of many statistical approaches, including descriptive analysis, research instrument analysis, multiple linear regression analysis, partial t-tests, and beta coefficient testing. The research presents a regression model expressed as Y = 30,465 - 0,511 (X1) + 0,173 (X2) – 0,264 (X3). At Garment Luwih Collection Grokgak, Bali, employee performance (Y) is influenced to some extent by the workload (X1), as shown by the negative regression coefficient b1X1. The positive correlation b2X2 suggests that competence (X2) has a partial impact on employee performance (Y) at Garment Luwih Collection Grokgak, Bali. The negative regression coefficient b3X3 suggests that job stress (X3) has a partial impact on employee performance (Y) at Garment Luwih Collection Grokgak, Bali. The variable of competence is the independent variable that has the greatest influence on employee performance, as shown by the Standardized Coefficients Beta value of 0,160.